The Brasilia Rules in Colombia - Robledo Silva, Paula (2020)
The Brasilia Rules are the result of an interesting effort made by the Ibero-American Judicial Summit, which sought to establish a code of conduct for states and the various public officials involved in the justice administration in order to guarantee effective access to justice for vulnerable groups. This work will focus on the evolutionary process of the Colombian legal system which, in the case of persons with disabilities, tends to improve the conditions for access to justice.